Is Community Participation in Urban Planning in Iskandar Malaysia Effective Enough ? A Qualitative Exploration - Khalid, Zanudin; Yusfida Ayu, Abdullah; Zafikha Aida, Bidin; Hamizah, Yakob; Andi, Zhang (Malaysian Institute of Planners, 2024)
This study aimed to evaluate the effectiveness of community participation in planning and operational decision-making in Iskandar Malaysia. The Iskandar Malaysia region consists of four local planning authorities who are responsible for planning and managing the spatial development in the region. Conceptually, effective community participation helps the local planning authority to make better decisions, hence, providing a sustainable and quality living environment. The study employed in-depth interviews to gather insights into the phenomenon from various key actors to address the questions. Following the 31 interviews performed, it is suggested that the effectiveness of community participation; and the incorporation of community interest in Iskandar Malaysia are substantially influenced by functional variables such as collaboration between stakeholders, community access to information and process, and intergovernmental relationships in planning. Structural and cultural variables include the skill and professionalism of public planners, the capability to influence, public awareness and knowledge, and community representation.